2015
DOI: 10.1007/s12020-015-0576-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between long-term proton pump inhibitor therapy and skeletal frailty

Abstract: Proton pump inhibitors (PPIs) are a commonly prescribed class of medications. Their use has been associated with an increased rate of fractures, most notably hip fractures. However, there does not seem to be a clear association between PPI use and bone mineral density measurements, assessed by dual X-ray absorptiometry. The mechanism by which PPI use increases the risk of fractures remains unclear. This review will summarize the current evidence on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Accordingly, key observations on the impact of each class on BMD and fracture risk are indicated in table 6, primarily in accordance with the findings of Panday et al in their 2014 review on medication-induced osteoporosis [81]. Recent literature reviews specific to each drug class are also cited to provide the reader with a source of more detailed current information [82][83][84][85][86][87][88][89][90][91]. A focus on three commonly used classes -glucocorticoids, androgen deprivation therapy and aromatase inhibitors -serves to illustrate the potential benefits of strategies to prevent osteoporosis induced by medicines.…”
Section: Osteoporosis Induced By Medicinessupporting
confidence: 67%
See 1 more Smart Citation
“…Accordingly, key observations on the impact of each class on BMD and fracture risk are indicated in table 6, primarily in accordance with the findings of Panday et al in their 2014 review on medication-induced osteoporosis [81]. Recent literature reviews specific to each drug class are also cited to provide the reader with a source of more detailed current information [82][83][84][85][86][87][88][89][90][91]. A focus on three commonly used classes -glucocorticoids, androgen deprivation therapy and aromatase inhibitors -serves to illustrate the potential benefits of strategies to prevent osteoporosis induced by medicines.…”
Section: Osteoporosis Induced By Medicinessupporting
confidence: 67%
“…Lau et al [89] Selective serotonin reuptake inhibitors Small studies have found an association between SSRI use and bone loss. However, meta-analysis has reported SSRI-related fractures in the absence of bone loss.…”
Section: Fls Model Proportion Investigated With Bmd Testing Proportiomentioning
confidence: 99%
“…In addition, peripheral neuropathy is also a consequence of vitamin B12 deficiency, increasing the risk of falls and, consequently, of bone fractures. The association between PPI use and increased risk of falls has been clearly demonstrated . Moreover, a direct PPI action on bone is also a possibility .…”
Section: Discussionmentioning
confidence: 99%
“…The association between PPI use and increased risk of falls has been clearly demonstrated. (24) Moreover, a direct PPI action on bone is also a possibility. (25) Osteoclast function is dependent on proton pumps, which may be directly inhibited by PPIs, reducing bone resorption and turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms have been recently reviewed and there is evidence implying an increased risk of falling by PPIs [20]. Future research is required to clarify the mechanisms for the prevention of fractures in elderly patients with PPI therapy.…”
Section: Dear Editormentioning
confidence: 99%